Neruda [videorecording (DVD)] - García Bernal, Gael, 1978-; Gnecco, Luis, 1962-; Morán, Mercedes (Sony Pictures Home Entertainment, 2017)
An inspector hunts down Nobel Prize-winning Chilean poet, Pablo Neruda, who becomes a fugitive in his home country in the late 1940s for joining the Communist Party.